IMPLEMENTASI PROGRAM TEACHING FACTORY (TEFA) BERBASIS UNIT PRODUKSI UNTUK MENINGKATKAN KOMPETENSI KEWIRAUSAHAAN SISWA DI SMK KEPARIWISATAAN BANDUNG RAYA - Suwandi, Andreas; Muktiarni, Muktiarni; Fitriyani, Endah; Setiadi, Raditya Pratama (LPPM Institut Pendidikan Nusantara Global, 2023)
Problems related to changes in the structure of employment opportunities in the era of the industrial revolution 4.0 and the existence of competency gaps faced by vocational schools in the field of tourism today. The SMK revitalization program that is currently running has a very important role as an effort to prepare SMK graduates to become skilled workers who are ready to work in various economic sectors such as agriculture, industry, tourism, and even the creative economy. This program also answers problems related to the preparation of superior human resources to process economic potential spread throughout Indonesia. The Teaching Factory is part of ten steps to revitalize vocational schools launched by the government, but it feels not optimal. This phenomenon arises so that vocational schools in the tourism sector can implement teaching factory programs in accordance with project-based learning. The research method uses a quantitative approach with secondary data collection techniques such as questionnaires and interviews. In addition, data collection in the form of tourism education curriculum is a source of data in primary data collection techniques. The analysis method uses quantitative content, exploratory, and descriptive analysis. The findings are expected to be able to answer the targets of this study which includes identifying the distribution of the SMK Tourism teaching factory management program in Bandung City based on project based learning to increase entrepreneurial interest of SMK students.